ANALISIS BIPLOT ROW METRIC PRESERVING UNTUK MENGETAHUI KARAKTERISTIK PROVIDER TELEPON SELULER PADA MAHASISWA S1 FSM UNIVERSITAS DIPONEGORO - Artha Ida Sri Anggriyani; Diah Safitri; Triastuti Wuryandari (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Communication is the basis of human interaction. One of the progression in telecommunications is telecommunication tools, e.g. a mobile phone. Usually on every communication tools such as mobile phones are equipped with a provider. The methods used to analyze mobile phone provider is the biplot analysis. Biplot analysis is an analysis which gives a demonstration of the matrix data graphically X into a plot with vector in row matrix X as describing an object, with a vector in column matrix X describing variables. If α = 1 then it is called analysis biplot Row Metric Preserving (RMP). The predictor variable used in this final project is the product, price, promotion and distribution. After analysis biplot, can be known that a two-dimensional graph biplot was able to explain 97,7% of actual data. The nearest competitor for Indosat provider is XL Axiata provider. Indosat provider winning in terms of promotions and distribution, Telkomsel provider winning in terms of products and Hutchison provider winning in terms of price. Keywords: telephone provider, Row Metric Preserving biplot, marketing mix